Broadline 1H NMR investigations of the mobility of polymers supported on carbonaceous particles and silica substrates - Hodgins, Genevieve R. (2020)
This research consists of two parallel investigations using solid state NMR to study the mobility of polymers adsorbed on substrates, the first is a study on the use solid state proton NMR as a testing methodology for deposit control additives, and the second is the investigation into the mobility of the carbon capture material; polyethylene imine supported on silica.